Modernization of Dense Wavelength Division Multiplexing (DWDM) Route Surabaya-Bangil To Increase Optical Network Capacity - Imelda Uli Vistalina Simanjuntak; Solichah Larasati; Yosy Rahmawati S; Dina Amalia Santika (ELKHA : Jurnal Teknik Elektro, 2022)
Along with the increasing demand for data networks, on the Java island network traffic, especially the Surabaya - Bangil link, the operator increases the channel capacity by modernizing DWDM (Dense Wavelength Division Multiplexing) technology in its transmission equipment. At that time, the DWDM technology was DWDM 6800 with a maximum capacity of one port that could only accommodate 10 Gbit/s, while using DWDM 9800, the maximum capacity of one port could accommodate up to 100 Gbit/s. Modernization of DWDM 6800 to DWDM 9800 technology uses the cross-connect method so that it does not require many costs and can be done within a short duration of time so that network performance can be adequately maintained. As a result, after modernization, the network has sufficient reserves to cover demand for the next few years.